Trasplante hepático adulto - Oksenberg R. , Danny (Revista Hospital Clínico Universidad de Chile, 2007)
In our environment experience and the outcome of orthotopic liver transplantation (OLT) were similar to that was observed in other countries. In Chile every year around 4.000 people die from cirrhosis of the liver and the waiting OLT list has grown, adding at present approximately 250 patients listed. It is therefore indispensable make an appropriate selection and ranking of patients for OLT. It describes the indications and contraindiciationes of OLT, and the steps to refer a patient to heart transplantation with their respective assessment. It discusses the characteristics of the donor, in terms of their selection to improve the outcome of surgery, such as surgical technique of the same. It sets of immunosuppression regimens with or without renal receiver, and finally, the definition and treatment of acute cellular rejection.